White Sand Black Beach : Civil Rights, Public Space, and Miamis Virginia Key - Bush, Gregory Wallace (Book collections on Project MUSE., 2016)
Combining archival research and oral history, Bush examines Virginia Key Beach as a window into local activism and forms of black-white dialogue in multicultural Miami from 1915 to 2012.